Ultramorphology of the root surface subsequent to hand-ultrasonic simultaneous instrumentation during non-surgical periodontal treatments: an in vitro study (Journal of Applied Oral Science, 2011)
OBJECTIVE: The purpose of this study was to investigate the ultramorphology of the root surfaces induced by mechanical instrumentation performed using conventional curettes or piezoelectric scalers when used single-handedly or with a combined technique. MATERIAL AND METHODS: Thirty single-rooted teeth were selected and divided into 3 groups: Group A, instrumentation with curettes; Group B instrumentation with titanium nitride coated periodontal tip mounted in a piezoelectric handpiece; Group C, combined technique with curette/ultrasonic piezoelectric instrumentation. The specimens were processed and analyzed using confocal and scanning electron microscopy. Differences between the different groups of instrumentation were determined using Pearson's χ2 with significance predetermined at α=0.001. RESULTS: Periodontal scaling and root planing performed with curettes, ultrasonic or combined instrumentation induced several morphological changes on the root surface. The curettes produced a compact and thick multilayered smear layer, while the morphology of the root surfaces after ultrasonic scaler treatment appeared irregular with few grooves and a thin smear layer. The combination of curette/ultrasonic instrumentation showed exposed root dentin tubules with a surface morphology characterized by the presence of very few grooves and slender remnants of smear layer which only partially covered the root dentin. In some cases, it was also possible to observe areas with exposed collagen fibrils. CONCLUSIONS: The curette-ultrasonic simultaneous instrumentation may combine the beneficial effects of each instrument in a single technique creating a root surface relatively free from the physical barrier of smear layer and dentin tubules orifices partial occlusion.